Water: The long road from Aristotelian element to H2O - Chang, Hasok (Circumscribere International Journal for the History of Science, 2012)
In today’s science-based civilization, people tend to accept without question the most basic things that science tells us. This is the case even for people who do not know much science or like it very much. For example, anyone with even the slightest acquaintance with modern science knows and accepts that water is H2O. Yet it was a very difficult thing for scientists to learn. That is the subject of my recently published book, Is Water H2O? Evidence, Realism and Pluralism (Dordrecht: Springer, 2012). If we take a closer look at the basic items of scientific knowledge that we take so much for granted, almost always we find that they were achieved only with great difficulty, and only after some very challenging questions were resolved, or set aside without being resolved.